Discover new perspectives and gain insights with IDNLearn.com. Our community is here to provide detailed and trustworthy answers to any questions you may have.

Part A: Solve the following equation: 8 + 2(x - 3) = 3x - 3

Sagot :

We need to solve the following equation:

[tex]8+2(x-3)=3x-3[/tex]

First we distribute the product in the left side:

[tex]\begin{gathered} 8+2(x-3)=3x-3 \\ 8+2x-6=3x-3 \end{gathered}[/tex]

Then we pass all the terms with an x to the left side and all the constant terms to right side:

[tex]\begin{gathered} 8+2x-6=3x-3 \\ 2x-3x=6-3-8 \\ -x=-5 \\ x=5 \end{gathered}[/tex]

So the answer is x=5.